DOES COVID-19 PANDEMIC AFFECT THE ELIMINATION OF TUBERCULOSIS? LESSONS LEARNED FROM INDONESIA - Utomo, Budi; Fatmaningrum, Widati; Sulistiawati, Sulistiawati; Khuen, Chan Chow; Fauziyah, Shifa; Adnyana, I Made Dwi Mertha; Eljatin, Dwinka Syafira; Sucipto, Teguh Hari (African Journal of Infectious Diseases (AJID), 2025)
Background: Tuberculosis is one of the tropical diseases which still exist in the tropical country specifically Indonesia. This study aims to investigate the recent epidemiology of tuberculosis before and during the pandemic of COVID-19. Materials and Methods: Data were collected from East Java Health Profile 2019 and 2020 which was provided by East Java Health Officer. Data were extracted and analyzed by statistical software SPSS and QGIS Application for the geographical map interpretation. Results: This study shows that the total cases of tuberculosis in 2019 was 606,985 cases, while in 2020 was decreased to 384,752 cases. The incidence rate of tuberculosis in 2019 was 224.98 per 100,000 populations, while in 2020 was 134.58 per 100,000 populations. The province with the highest amount of tuberculosis in 2019 was West Java with 143,935 cases, and also in 2020 with 90,905 cases. The province with the lowest number of tuberculosis was North Kalimantan with 2,113 cases, while in 2020 were 985 cases. The highest incidence rate of tuberculosis in 2019 was found in Jakarta which was 443,47 per 100,000 population, while in 2020 was found in Papua which was 279.92 per 100,000 population. The lowest incidence rate in 2019 was found in Bali Province which was 102.72 per 100,000 population, while in 2020 was 67.43 per 100,000 population. Conclusion: There was a decrease in TB cases before the COVID-19 pandemic (2019) compared to during the COVID-19 pandemic (2020).